Prediksi Penyakit Demam Berdarah Dengue (Dbd) Dan Tifus Menggunakan Jaringan Syaraf Tiruan Perambatan Balik (Back Propagation) - Farida Asriani; Hesti Susilawati; Lucyana Harvianti (Dinamika Rekayasa, 2007)
Dengue Haemorrhagic Fever (DHF) and Typhus are diseases which often knock over Indonesian society. Both of these diseases, especially DBD is malignancy that able to result death if losing time to be diagnosed. But civil society, even a doctor which is expert, sometimes also difficult to detect DHF diagnosed earlier, because symptom initially, tending to look like with other acute diseases. One of the diseases that have symptom like DHF is typhus. Back Propagation Artificial Neural Network (ANN) is one of artificial intelligences that can be applicated in the field of health, especially for predicting a disease type. By using input in the form of symptoms the naturalness by a patient, expected this Back Propagation ANN system can help the doctors to diagnose the diseases that happen to their patients, especially DHF and Typhus diseases. ANN system that is designed to predict DHF and typhus diseases, is trained with back propagation algorithm that using adaptive learning rate and momentum. From this research, is got ANN system with network architecture that consist of: one input layer with 18 neurons, one hidden layer with 125 neurons, and one output layer with 1 neuron. And also, value of constanta momentum is 0.95.This ANN system has good performance. From 400 respondents that use for training, result of the memorizing examination reaches percentage equal to 100%, and result of the generalizing examination reaches 96%, from 150 new respondents